DEFINITION OF ENVIRONMENTAL THREATS IMPOSED BY FILLING STATIONS ACTIVITY - Radomska, Margaryta; Golovko, Anna (Proceedings of National Aviation University (archive), 2014)
The role of green space was considered in the paper. The basic negative impacts on the quantity and quality of green spaces were defined. It was set that the optimization of green areas exploitation is main prerequisite of the urban environment improvement which requires their comprehensive study, assessment of natural resource potential and its possible changes, study of the approaches to their use without damage to nature and people to be. The implementation of proposed recommendations within geoecological approach allows to detect complex structural and functional properties of green spaces geosystem as natural objects and finding ways for their improvement.